Design of a Rotary Table Hydroponic System for Agricultural Improvement in Limited Urban Land - Predi Maulana Putra; Leni, Desmarita; Muchlisinalahuddin, Muchlisinalahuddin; Hendra, Hendra; Kusuma, Yuda Perdana (IJIMCE : International Journal of Innovation in Mechanical Construction and Energy, 2024)
This research focuses on the design of a rotary table hydroponic device for effective, efficient, and space-saving plant growth. With machine dimensions of 1570 x 600 x 2360 mm, a frame made of 2 mm thick 30 x 30 mm galvanized hollow steel, and a 1.5 HP electric motor, the machine is engineered to maximize land utilization in hydroponic methods. Stress analysis on the frame reveals maximum and minimum values of 3,631e+01 MPa and 2,064e-03 MPa, respectively, while the safety factor reaches 1,211e+05 and 6,886e+00, surpassing the safety factor range for static loads. The results of this experiment confirm the effectiveness and safety of the design, demonstrating that this rotary table hydroponic device can be optimally utilized in hydroponic plant cultivation.